2015
DOI: 10.1111/jace.13676
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Study of Sc1−xTixF3 (x ≤ 0.375): Negative Thermal Expansion, Phase Transition, and Compressibility

Abstract: We present the first‐principles investigation of boldSc1−xboldTiboldxboldFbold3 (x ≤ 0.375). Controllable thermal expansion of boldSc1−xboldTiboldxboldFbold3 is achieved by different Ti contents. The negative thermal expansion (NTE) behavior is weakened gradually with increasing Ti content, which is consistent with experimental measurements. The Jahn–Teller effect plays an important role in the cubic‐to‐rhombohedral phase transition, which stems from the enhanced energy stability when the 3d orbitals of Tibold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…To elucidate the unique thermophysical properties of ScF 3 , accurate treatment of lattice dynamics including anharmonic effects is essential. Since the discovery of the large NTE in ScF 3 , several first-principles studies based on density functional theory have reported the CTE calculated within the quasi-harmonic approximation (QHA) [20][21][22]. Since the QHA only accounts for the volume dependence of phonon frequencies and neglects higher-order anharmonicities, however, none of these QHA results correctly reproduced the experimental CTE values.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the unique thermophysical properties of ScF 3 , accurate treatment of lattice dynamics including anharmonic effects is essential. Since the discovery of the large NTE in ScF 3 , several first-principles studies based on density functional theory have reported the CTE calculated within the quasi-harmonic approximation (QHA) [20][21][22]. Since the QHA only accounts for the volume dependence of phonon frequencies and neglects higher-order anharmonicities, however, none of these QHA results correctly reproduced the experimental CTE values.…”
Section: Introductionmentioning
confidence: 99%
“…ScF 3 has attracted a lot of interest for its negative thermal expansion [16,18,[33][34][35][36][37][38][39][40]. The crystal structure is shown in Fig.…”
mentioning
confidence: 99%
“…In addition, the Gruneisen equation can also be used to express the relationship between the CTE of a material and temperature [25]. This is expressed by the mode Gruneisen equation as:…”
Section: Thermal Expansion Model Of Compositesmentioning
confidence: 99%